2008
DOI: 10.1007/s00405-008-0815-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cochlear implantation on horizontal semicircular canal function

Abstract: The objective of this study was to assess the influence of a cochlear implant (CI) on horizontal semicircular canal (hSCC) function, to test the correlation with symptomatic vertigo and to identify possible risk factors for a postoperative vestibular impairment. In a prospective observational study design, forty-seven adult patients who had undergone cochlear implantation at Cochlear Implant Center at a tertiary referral university hospital, Munich, between 2003 and 2007, were studied. Postoperative vertigo sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…Presumably, in other studies patients might have accommodated to whatever balance ability they were left with following surgery and might not accurately recall their more acute symptoms immediately after surgery. The finding that subjective and objective changes did not correlate well is consistent with previous observations that end-organ function is only poorly correlated with subjective impressions of balance in both cochlear implant patients as well as others Krause et al, 2009Krause et al, , 2010Mbongo et al, 2007].…”
Section: Subjectivesupporting
confidence: 79%
See 2 more Smart Citations
“…Presumably, in other studies patients might have accommodated to whatever balance ability they were left with following surgery and might not accurately recall their more acute symptoms immediately after surgery. The finding that subjective and objective changes did not correlate well is consistent with previous observations that end-organ function is only poorly correlated with subjective impressions of balance in both cochlear implant patients as well as others Krause et al, 2009Krause et al, , 2010Mbongo et al, 2007].…”
Section: Subjectivesupporting
confidence: 79%
“…Previous estimates of subjective imbalance after cochlear implantation have ranged from about one third to three quarters of implantees [Enticott et al, 2006;Fina et al, 2003;Krause et al, 2009Krause et al, , 2010Steenerson et al, 2001], although one article did report an improvement in subjective balance after surgery [Buchman et al, 2004]. One reason for our estimate being at the higher end of previously reported rates may be that we collected data within 2 weeks of surgery, whereas other studies included data from subjects tested over months to years postoperatively.…”
Section: Subjectivecontrasting
confidence: 53%
See 1 more Smart Citation
“…Besides morphological changes, a CI also causes functional damage of vestibular parts of the labyrinth, but these findings did not lead to vertigo complaints. Other senses as visual afferents and central vestibular compensatory mechanisms play a role in order to the patient stay asymptomatic [23].…”
Section: Resultsmentioning
confidence: 99%
“…Possible underlying mechanisms may include direct trauma caused by electrode insertion, acute serous labyrinthitis, reaction to a foreign body, endolymphatic hydrops, and electrical stimulation [Katsiari et al, 2013;Ibrahim et al, 2017]. Multiple studies have demonstrated damage to the semicircular canals [Buchman et al, 2004;Migliaccio et al, 2005;Enticott et al, 2006;Filipo et al, 2006;Kluenter et al, 2009Kluenter et al, , 2010Krause et al, 2009Krause et al, , 2010 and otolith organs [Basta et al, 2008;Melvin et al, 2009;Krause et al, 2010]. A recent review showed a significant negative effect on the results of caloric as well as vestibular-evoked myogenic potential tests [Ibrahim et al, 2017].…”
Section: Introductionmentioning
confidence: 99%